2016
DOI: 10.1002/14651858.cd006641.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Rooming-in for new mother and infant versus separate care for increasing the duration of breastfeeding

Abstract: We found little evidence to support or refute the practice of rooming-in versus mother-infant separation. Further well-designed RCTs to investigate full mother-infant rooming-in versus partial rooming-in or separate care including all important outcomes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
2
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 44 publications
5
78
2
6
Order By: Relevance
“…Other barriers include the participants' experience of breastfeeding; the perception both breast milk and formula were not nutritious enough to feed the baby to six months of age. Similar results were documented in Mozambique [20,21] and other African countries [48][49][50][51]. Moreover, participants struggled to maintain the expected physical growth and ideal weight of their babies to avoid reprimands from the nurses rather than preventing malnutrition.…”
Section: Discussionsupporting
confidence: 67%
“…Other barriers include the participants' experience of breastfeeding; the perception both breast milk and formula were not nutritious enough to feed the baby to six months of age. Similar results were documented in Mozambique [20,21] and other African countries [48][49][50][51]. Moreover, participants struggled to maintain the expected physical growth and ideal weight of their babies to avoid reprimands from the nurses rather than preventing malnutrition.…”
Section: Discussionsupporting
confidence: 67%
“…Several studies have demonstrated the importance of the rooming-in for breastfeeding, providing greater confidence to the mother in relation to the latch-on and proper positioning for breastfeeding, autonomy to understand and care for the child, in addition to providing increased interaction between mothers and health professionals, which can take advantage of this environment to address essential aspects to enhancing the effectiveness of breastfeeding 44,45 . Cochrane systematic review found that the prevalence of exclusive breastfeeding until the fourth day before hospital discharge was higher among women who remained rooming-in than among those who were separated from their child 46 .…”
Section: Discussionmentioning
confidence: 99%
“…35 Hospital staff members caring for mother-infant dyads have more opportunities to empower mothers to care for their infants than when infant care is conducted without the mother and in a separate nursery. For the breastfeeding mother-infant dyad, rooming-in may help to support cuebased feeding, leading to increased frequency of breastfeeding, especially in the first few days 36 ; decreased hyperbilirubinemia; and increased likelihood of continued breastfeeding up to 6 months. 37 SSC and rooming-in are 2 of the important steps in the WHO's "Ten Steps to Successful Breastfeeding" and serve as the basic tenets for a baby-friendly-designated delivery hospital.…”
Section: Evidence For Ssc and Rooming-inmentioning
confidence: 99%